Meteoritic Molybdenum and Ruthenium Isotopic Abundances Document Nucleosynthetic p-process Components - Marti, Kurt; Fischer-Gödde, Mario; Proksche, Carina (Astrophysical Journal, 2023)
Anomalies in isotopic abundances of Mo and Ru in solar system matter were found to document variable contributions of the nucleosynthetic s-process component. We report isotopic relations of ϵ 92Mo versus ϵ 100Ru in meteorites from chondritic parent bodies, iron meteorites, and achondrites that reveal deviations from expected s-process abundance variations. We show that two p-process isotopes 92Mo and 94Mo require the presence of distinct p-process components in meteoritic materials. The nucleosynthetic origin of abundant magic (N = 50) p-process nuclides, covering the mass range of Zr, Mo, and Ru, has long been an enigma, but contributions by several recognized pathways, including alpha and νp-antineutrino reactions on protons, may account for the observed relatively large solar system abundances. Specific core-collapse supernovae explosive regions may carry proton-rich matter. Since Mo and Ru isotopic records in solar system matter reveal the presence of more than one nucleosynthetic p-process component, these records are expected to be helpful in documenting different explosive synthesis pathways and the implied galactic evolution of p-nuclides.
CRIS-Team Scopus Importer:2023-11-03